2011
DOI: 10.1161/circulationaha.110.007864
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding Risk in Very Old Patients on Vitamin K Antagonist Treatment

Abstract: Background-Vitamin K antagonist (VKA) therapy is increasingly being used for the prevention of venous thromboembolism and stroke in atrial fibrillation. Bleeds are the major concern for VKA prescription, especially in very old patients who carry many risk factors for bleeding. We performed a large multicenter prospective observational study that enrolled very old patients to evaluate the quality of anticoagulation and the incidence of bleedings. Methods and Results-The study included 4093 patients Ն80 years of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(68 citation statements)
references
References 23 publications
(21 reference statements)
4
60
2
2
Order By: Relevance
“…These findings are similar to those of the BAFTA study [63]. A large multicenter study that enrolled very old patients concluded that the rate of bleeding is low (1.87 major hemorrhages per 100 patientyears; 26 fatal bleeding events, rate of 0.27 per 100 patient-years) [72]. Tincani et al followed ninety patients aged 90 years or older with nonvalvular AF and taking anticoagulants, and found low rates of bleeding and thromboembolism.…”
Section: Falls and Bleeding Risksupporting
confidence: 82%
“…These findings are similar to those of the BAFTA study [63]. A large multicenter study that enrolled very old patients concluded that the rate of bleeding is low (1.87 major hemorrhages per 100 patientyears; 26 fatal bleeding events, rate of 0.27 per 100 patient-years) [72]. Tincani et al followed ninety patients aged 90 years or older with nonvalvular AF and taking anticoagulants, and found low rates of bleeding and thromboembolism.…”
Section: Falls and Bleeding Risksupporting
confidence: 82%
“…In our old lady, we observed an initial marked increase of INR values determined by a misinterpretation of warfarin prescription. At this regard, to limit the hemorrhagic complications of an oral anticoagulant regimen in the elderly, it has been shown that it is necessary to have a careful management plan conducted by experienced centers [8]. In our patient, we observed an important instability of INR and a related low time in therapeutic range (TTR), even after having begun a more solicitous monitoring protocol.…”
Section: Discussionmentioning
confidence: 69%
“…In clinical and pharmacogenetic models for predicting maintenance dose, age is associated with lower dose requirements [77]. Low dose VKA initiation algorithms have been suggested in the elderly to reduce bleeding complications [78] as the initial phase of AC is the period at highest haemorrhagic risk [79]. Several bleeding scores have been developed in the setting of VTE [80][81][82][83], but a recently published analysis on patients from the Swiss national VTE cohort showed poor performance of all these scores in patients N65 years (area under the ROC curves ranging from 0.49 to 0.6) [84].…”
Section: Managing the Switch To Vkas In Elderly Patients With Pementioning
confidence: 99%
“…Intensity of AC is a major determinant of haemorrhagic complications [85], with an exponential increase in bleeding risk with INRs N 4.5 regardless of age [86]. A recent prospective study including more than 4000 elderly patients N 80 years naïve to VKA in whom VKA was initiated (25% with VTE) showed a low rate of major bleeding (1.87 per 100 patient-years) in these patients followed-up in Italian anticoagulation clinics (median time in therapeutic range 62%) suggesting that careful monitoring can highly improve the security of VKAs even in very old patients [79]. Patient information is also essential and reduces AC-related haemorrhagic complications in elderly patients [87].…”
Section: Managing the Switch To Vkas In Elderly Patients With Pementioning
confidence: 99%